THE APPLICATION OF GOOD HABITS IN ENHANCING HUYULA-BASED CHARACTER EDUCATION AMONG STUDENTS AT SMP NEGERI 3 KABILA, BONE BOLANGO REGENCY - Hidayatullah S. Timumu; Lucyane Djaafar; Rahmatiah (SOSIOEDUKASI, 2026)
This study aims to analyze the implementation of good habits in enhancing Huyula-based character education among students at SMP Negeri 3 Kabila. The method used is a descriptive qualitative approach, employing data collection techniques such as observation, in-depth interviews, documentation, and literature review, involving the school principal, teachers, students, and parents. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of good habits is carried out through the cultivation of literacy, study discipline, cooperation, community service, social awareness, as well as the strengthening of moral knowing, moral feeling, and moral action within the school culture. These habits contribute to the development of discipline, responsibility, mutual cooperation, and moral awareness among students, although behavioral consistency is still influenced by the social environment and gadget use. The novelty of this study lies in the integration of the concept of good habits with the local Huyula values as an approach to character building based on sustainable social habit formation.